A study of Jin Zhimang’s life and works - Yip, Ching Yon (2014)
Jin Zhimang (1912-1988), aka Chen Shuying (陈树英), was born during the crossroads of two eras. Deeply influenced by revolutionary thoughts, he used to stand up bravely against unfairness. Like many other Chinese intellectuals, he taught in school and at the same time wrote frequently after his arrival at the Nanyang in 1936. Honoured as one of the ground-breaking founder for the localized Malaysian Chinese literature, he was also known as a great writer in the leftist Chinese Malayan literary circle. Besides novels, Jin’s works also include literary commentaries. He was also the editor for newspaper which was very significant for that particular era such as Ipoh Daily, Minsheng Bao and the tabloid Combantant Friends. Jin’s literary works are based on the local setting. His writings entitled ‘About the Chinese Malayan Creative Writing’ as well as ‘The Creative Writing of the Immigrants’ are among the most important works in the history of the Chinese Malay(si)an literature. After WWII, the British colonial government declared a state of emergency in Malaya and started its suppression against the Malayan Communist Party. Jin decided to join the underground anti-British rebellion force then. During that period of time, Jin completed some of his anti-British warfare short stories, novels and other literary works. Due to the sensitive atmosphere in the post-war era, most of the critics tried not to give positive reviews to Jin’s works. For example, Mr. Fang Xiu, one of the leading scholars of Chinese Malayan literature, only commented on Jin’s works at the early times saying that ‘Jin has created a series of literary works reflecting the most active patriotic movements pertaining to the early periods of wartime.’ Meanwhile, other scholars revealed that Jin’s works, to some extent, described the struggle of the Malayan Chinese during the difficult times, through various metaphors to emphasize their noble cause for the preservation of their ethnic culture and education. Despite often being labeled as a ‘south-bound author’, his passion as well as the contributions and sacrifices he made towards Nanyang, the land which he decided to settle down, are unarguably more significant than that of other local-born authors and citizens. The exclusive ideologies he incorporated into some of the thought-provoking articles he published during the Japanese occupation and post-war era have been influential to the development of the Malayan Chinese literature. This article will elaborate on Jin’s philosophy with regard to his literary principles in order to give a proper and appropriate insight into the literary works of Jin. Keywords:Jin Zhimang, Malaysian Chinese leftist literature, south-bound authors, the uniqueness of the Malaysian Chinese literature.